THE FETISH OF SCIENCE-MERCHANDISE, THE SCIENTIST AS MERCHANDISE AND TECHNOLOGICAL DOMINATION - Queiroz Neto, Valdemir Pereira de; Severiano, Maria de Fátima Vieira (Cadernos de Educação Tecnologia e Sociedade, 2020)
This article has the objective of promoting reflections on the Technological Rationality and its implications to the production of science and the educational formation of scientists. With support on the theoretical reference of the Frankfurt School and other thinkers of the issue of technique and science, a critic is addressed to the existing disequilibrium between technical and humanitarian progress, denouncing the need of a redirection of scientific propositions to human needs and to the combat of the ever-increasing social inequality. Methodologically, this article is constituted of a theoretical discussion about the matter of the use of science as an instrument capable of enhancing the dominations directed to individuals, both scientists and consumers of science products. The findings reinforce the importance of the recovery of social and political values in science to the construction of a fairer and more balanced society.